royQV wrote:

Dear MacFauz

Answer is C

I do understand that C is the correct choice but can you please explain why e is wrong?

I think you are assuming that (X^Y) + (X^Z) is = (X^Y+Z) which is not true, as it only applies to multiplication. Rather it would have to be (X^Y)(X^Z) = (X^YZ)

So when you simplify down to 2^48 + 2^52 + 2^48 you cannot just add exponents.

Here's how my brain works with this one,

Step 1: Recognize a common base.

(8^16) + (16^13) + (4^24) = ((2^2)^16) + ((2^4)^13) + ((2^2)^24) = (2^48) + (2^52) + (2^48)

Step 2: Recognize the factor and pull out of the equation.

= (2^48)(1 + (2^4) + 1)

= (2^48)(1 + 16 + 1)

= (2^48)(18)

Step 3: Recognize this is not an answer and adapt.

(2^48)(18) = (2^48)(2)(9) = (2^49)(9)

Answer is C.